SPEECH AND LANGUAGE IMPAIRMENT AFTER CHILDHOOD ARTERIAL ISCHEMIC STROKE - Akhtar, Muhammad; Khalily, Muhammad Athar; Ghani, Natasha; Sultan, Tipu (Pakistan Armed Forces Medical Journal, 2023)
Abstract Objective: Investigate the potential predictors’ dysarthria and dyspraxia of speech and language impairment after childhood stroke. Study Design: Cross sectional study Place and duration of study: Study was conducted in the department of Paediatric Neurology, The Children’s Hospital & Institute of Child Health, Lahore for about one year i.e. from 31st August 2019 to 31st August 2020. Methodology: Seventy children of radiological diagnosed arterial ischemic stroke were selected for study. Prevalence of dyspraxia and dysarthria and language impairment was measured within 2 weeks of stroke. Side of stroke (right, left or both) were assessed and proportion of language impairment, dysarthria, dyspraxia was measured in this study. SPSS version 23 was used for data analysis and determination of variables. P values of ≤0.05 were considered as significant. Results: Seventy patients were included in this study. The mean age of the patients was 8.11±1.26 years. Stroke effects on left side was noted in 27 (38.6%) cases, stroke effects on right side was noted in 33 (47.1%) cases, while in 13 (18.6%) cases both Hemispheres were involved, dysarthria was present in 50 (71.4%) cases, language impairment was observed in 45 (64.3%) cases and verbal dyspraxia was noted in 12 (17.1%) cases. Conclusion: Long term cognitive, motor and neurological outcomes are the results of arterial ischemic stroke. Dysarthria, language impairment and dysparaxia are the main affects of stroke that dependant on size and place lesion. Rehabilitation cannot be predicted after childhood stroke. Keywords: Apraxia; Brain injury; Child; Dysarthria; Language; Stroke; Speech.